1991
DOI: 10.1177/154079699101600402
|View full text |Cite
|
Sign up to set email alerts
|

Medical Conditions, Level of Care Needs, and Health-Related Outcomes of Persons with Mental Retardation: A Review

Abstract: A literature review wasconducted to analyze existing data on health needs ofpeople with mental retardation and possible barriers to integration in the community. Information was obtained on medical conditions, level ofcare needed, and health-related outcomes. The type and range of medicalcare, resources, and support servicesneededto maintain individuals with medicalproblems were identified, as were barriers to and recommendations for the provision of community-based medical care. Although there are barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Asberg 1989). Hayden & DePaepe (1991) have pointed out that paying attention to the health-related needs of people with learning disabilities is a challenge for community-based services, and Lindsay (1991) has made a similar point about the psychological health of clients, arguing that persons with learning disabilities should have access to the same range of psychological therapies as other citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Asberg 1989). Hayden & DePaepe (1991) have pointed out that paying attention to the health-related needs of people with learning disabilities is a challenge for community-based services, and Lindsay (1991) has made a similar point about the psychological health of clients, arguing that persons with learning disabilities should have access to the same range of psychological therapies as other citizens.…”
Section: Discussionmentioning
confidence: 99%
“…The existing research suggests that, with few exceptions, the prevalences of chronic health conditions (including cardiovascular disease, cancer, lung conditions, and diabetes) in individuals with mental retardation are similar to those in the general population. 3,[7][8][9] Understanding the risk factors for secondary conditions and strategies for their prevention is important to people with disabilities, rehabilitation service providers, and public health agencies. A study of secondary conditions among adults with developmental disabilities in Montana reported limitations due to communication problems, poor physical fitness, low frustration tolerance, and weight problems.…”
mentioning
confidence: 99%
“…They are faced with many challenges in understanding and maintaining their health (Barr, 1999) and lack access to adequate health services (President's Committee on Mental Retardation, 1999). In fact, the health care needs of people with ID and their access to quality health services has been of limited research concern (Garrard, 1982;Hayden & DePaepe, 1991;Ziring, Katsner, Friedman, Pond, Barnett, Sonnenberg, & Strassburger, 1988). A recent review of the literature by Hayden, Kim, and DePaepe (2005) found that people with ID and significant medical conditions, who live in the community, receive disparate treatment.…”
mentioning
confidence: 99%